Implementasi Pembelajaran Berdiferensiasi Untuk Mengakomodasi Kebutuhan Belajar Peserta Didik Pada Mata Pelajaran Bahasa Indonesia Di SMP Negeri 1 Aikmel - Misnawati, Misnawati; Nursaly, Baiq Rismarini; Mohzana, Mohzana (Educatio, 2024)
This research aims to explore how teachers at SMP Negeri 1 Aikmel design different learning experiences to accommodate the diverse learning needs of students. The main focus of this research is on the implementation of differentiated learning, an approach that allows teachers to adapt teaching strategies to the diversity of student learning styles. Through a descriptive qualitative approach, data is collected through interviews, observation and documentation. The results showed that this approach contributed positively to student understanding and engagement, although some students faced challenges in adapting learning methods. Thus, differentiated learning has proven to be effective in creating an inclusive learning environment and supporting students' academic success and character development.